Penentuan agenda nasionalisme Tun Dr. Mahathir Mohamad - Mohd Norhaizzat Naim, Mohd Mazlan (2019)
Tun Dr. Mahathir Mohamad is the longest-serving UMNO and Prime Minister in developing Malaysia. Holding the administration as Prime Minister for 22 years made him a Malay nationalist and figure identifier and symbol of the rise of the Malays. This study was conducted to identify the meaning of nationalism that shaped the development agenda of Malaysian nationalism through the text of the speech of the UMNO General Assembly, identifying the media coverage of the nationalism agenda in the newsroom in the special room of the UMNO General Assembly and identifying public perceptions of Tun's leadership in developing nationalism Malaysian citizen. This study is guided by the Agenda Setting Theory by using a qualitative approach. Content analysis is done on speech and newspaper texts to get the meaning and agenda of nationalism. While the interview was conducted to see the perception of the audience towards Tun's leadership. The analysis of this study uses thematic analysis. The findings show the six dimensions of unity, responsibility, dignity, loyalty, sacrifice and advancement of the major themes that give meaning to nationalism in Tun's thinking. The entire study of the newspaper, the study shows the News Strait Times does not give any emphasis on the aspects highlighted by Tun. The study also found that economic, social and political aspects are the most emphasized aspects of the press. While culture and religion are not given emphasis and the aspect of education is not covered by the press. Furthermore, this study also found the audience acknowledging the power of Tun's leadership in developing Malay ethnic nationalism. Based on the findings of the study processed through the Agenda Determining Theory, the content (meaning of nationalism) contained in Tun's texts and press coverage affects the development of nationalism in society.